The Effect of Antenatal Care Quality on Maternal Mortality Rate in Central Sulawesi, Indonesia - Suarayasa, Ketut; Hermiyanti; Wandira, Bertin Ayu; Rizki Ashari, Muhammad; Pitriani; Yani, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
In order to reduce maternal mortality rate there should be providing high-quality antenatal care services and increasing delivery assistance by trained healthcare personnel. This study aimed to obtain a picture of the quality of antenatal care and its effect on maternal mortality rate. In order to reduce maternal mortality rate there should be providing high-quality antenatal care services and increasing delivery assistance by trained healthcare personnel. This study aimed to obtain a picture of the quality of antenatal care and its effect on maternal mortality rate. There were 3 low ANC standards in the implementation: Hb examination, counseling and Case Management. While the quality of Antenatal Care (ANC) had a risk of 6.609 times increasing the maternal mortality rate (OR = 6.609) and was a significant factor in maternal mortality rate in Central Sulawesi (1,823-23,952). The implementation of Antenatal Care is still low and ANC is the significant factor in the maternal mortality rate. Therefore, the quality of Antenatal Care needs to be improved through the implementation of 10 Antenatal Care Standards accurately.